Thermoacidophilic Bioleaching of Industrial Metallic Steel Waste Product - Kölbl, Denise; Memic, Alma; Schnideritsch, Holger; Wohlmuth, Dominik; Klösch, Gerald; Albu, Mihaela; Giester, Gerald; Bujdoš, Marek; Milojevic, Tetyana (Frontiers in Microbiology, 2022)
The continuous deposition of hazardous metalliferous wastes derived from industrial steelmaking processes will lead to space shortages while valuable raw metals are being depleted. Currently, these landfilled waste products pose a rich resource for microbial thermoacidophilic bioleaching processes. Six thermoacidophilic archaea (Sulfolobus metallicus, Sulfolobus acidocaldarius, Metallosphaera hakonensis, Metallosphaera sedula, Acidianus brierleyi, and Acidianus manzaensis) were cultivated on metal waste product derived from a steelmaking process to assess microbial proliferation and bioleaching potential. While all six strains were capable of growth and bioleaching of different elements, A. manzaensis outperformed other strains and its bioleaching potential was further studied in detail. The ability of A. manzaensis cells to break down and solubilize the mineral matrix of the metal waste product was observed via scanning and transmission electron microscopy. Refinement of bioleaching operation parameters shows that changes in pH influence the solubilization of certain elements, which might be considered for element-specific solubilization processes. Slight temperature shifts did not influence the release of metals from the metal waste product, but an increase in dust load in the bioreactors leads to increased element solubilization. The formation of gypsum crystals in course of A. manzaensis cultivation on dust was observed and clarified using single-crystal X-ray diffraction analysis. The results obtained from this study highlight the importance of thermoacidophilic archaea for future small-scale as well as large-scale bioleaching operations and metal recycling processes in regard to circular economies and waste management. A thorough understanding of the bioleaching performance of thermoacidophilic archaea facilitates further environmental biotechnological advancements.